Prevalence and Associated Factors of Liquid-Based Cytology (LBC) Results among Women Attending a Tertiary Cancer Hospital of Central Nepal - Subedi, Hemnath; Acharya, Bijaya Chandra; Rana, Sarita; Kaduwal, Shankar; Paudel, Sumita; Sharma, Manju; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2025)
Background Cervical cancer remains a leading cause of morbidity and mortality among women worldwide. Early detection is crucial for prevention and management. Liquid-Based Cytology (LBC) offers more accurate screening compared to traditional Pap smears. This study aimed to find the prevalence and associated factors of LBC positivity among women at a tertiary cancer hospital in central Nepal. Methods A hospital-based analytical cross-sectional study was conducted among 987 women aged 30–50 years attending the Gynaecology OPD of B.P. Koirala Memorial Cancer Hospital from July 2024 to March 2025. LBC results were the dependent variable, and demographic, reproductive, and family-related factors were independent variables. Data were entered and analyzed using SPSS and R; descriptive and inferential statistics were applied, with p-value < 0.05 considered significant. Results The prevalence of positive LBC results was 6.9% (95% CI: 5.31% to 8.4%). Among the 56 women with positive LBC, 89% had menarche before age 15, and 34% were aged 40–45 years. Contraceptive use (p-value < 0.001), bleeding during sexual intercourse (p-value = 0.043), and number of deliveries (p-value = 0.02) were significantly associated with LBC positivity. Conclusions The study revealed a moderate prevalence of positive LBC results among women aged 30–50 years at a tertiary cancer hospital in Nepal. Significant associations included bleeding during sexual intercourse, contraceptive use, and number of deliveries. These findings underscore the importance of regular screening and increased awareness to reduce cervical cancer burden in Nepal.